2011
DOI: 10.1093/pubmed/fdr031
|View full text |Cite
|
Sign up to set email alerts
|

Less exercise and more TV: leisure-time physical activity trends of Shanghai elders, 1998-2008

Abstract: In comparison to 1998, for Shanghai elders, the trend for engaging in leisure-time habits not related to physical activity increased over time, becoming statistically significant in 2005 and 2008 (e.g. OR for watching TV in 2003, 2005 and 2008 is 1.04 [0.91, 1.19], 1.17 [1.00, 1.38] and 1.78 [1.51, 2.09], respectively). Simultaneously, the trend for engaging in regular exercise declined significantly in each observation year in comparison to 1998 (OR in 2003, 2005 and 2008 is 0.70 [0.61, 0.80], 0.36 [0.30, 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Urban populations worldwide are growing at a faster rate than rural residents, but particularly in China because of rapid urbanization and large rural-urban migration (Shen, Feng, & Wong, 2006; Zhang & Song, 2003), which by the end of 2008 will cause the urban population growth in China to equal the total population growth in this country throughout recorded history (United Nations Population Fund, 2007). Overcrowding, poverty, greater levels of pollution or environments that preclude safe recreation and/or physical activity have all been proposed as possible explanations for why city residence might promote dependency in aging (Feng, Purser, Zhen, & Duncan, 2011; United Nations Population Fund, 2007; Zeng, Gu, Purser, & Hoenig, 2007). There could alternatively be substantial unmet needs in rural environments if the low self-reported dependence in ADLs is not due to better health per se but due to inadequate resources available to allow physically limited individuals to depend on others or on equipment for assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Urban populations worldwide are growing at a faster rate than rural residents, but particularly in China because of rapid urbanization and large rural-urban migration (Shen, Feng, & Wong, 2006; Zhang & Song, 2003), which by the end of 2008 will cause the urban population growth in China to equal the total population growth in this country throughout recorded history (United Nations Population Fund, 2007). Overcrowding, poverty, greater levels of pollution or environments that preclude safe recreation and/or physical activity have all been proposed as possible explanations for why city residence might promote dependency in aging (Feng, Purser, Zhen, & Duncan, 2011; United Nations Population Fund, 2007; Zeng, Gu, Purser, & Hoenig, 2007). There could alternatively be substantial unmet needs in rural environments if the low self-reported dependence in ADLs is not due to better health per se but due to inadequate resources available to allow physically limited individuals to depend on others or on equipment for assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if education shapes psychological well-being in late life, it may do so in part through leisure-time activities engaged in by the elderly. Other types of activities such as playing cards/mahjong, attending organized social activities, and readings that may stimulate cognitive abilities or enhance social interactions are often overlooked in this literature, although some studies suggest that these nonexercise leisure activities may have different prevalence and trends among older Chinese over time (Feng, Purser, Zhen, & Duncan, 2011). Other types of activities such as playing cards/mahjong, attending organized social activities, and readings that may stimulate cognitive abilities or enhance social interactions are often overlooked in this literature, although some studies suggest that these nonexercise leisure activities may have different prevalence and trends among older Chinese over time (Feng, Purser, Zhen, & Duncan, 2011).…”
Section: Pathways Linking Education and Healthmentioning
confidence: 99%
“…Television ownership and the use of many other screen-based devices have also proliferated in Chinese households, so that leisure-time pursuits have become increasingly sedentary. For example, a recent study found that the proportion of Shanghai elderly who identified TV viewing as the most common leisuretime activity increased from 66% in 1998 to 78% in 2008 [15]. As a result of changes in diet, physical activity, and sedentary behavior, the prevalence of overweight and obesity among Chinese adults increased from 23% and 7% in 2002 to 31% and 12% in 2010 [16].…”
Section: Economic Growth Lifestyle Changes and Ncds In Chinamentioning
confidence: 99%